Impairment in Attention Focus During the Posner Cognitive Task in Children With ADHD: An Eye Tracker Study - Caldani, Simona; Isel, Frederic; Septier, Mathilde; Acquaviva, Eric; Delorme, Richard; Bucci, Maria Pia (Frontiers in Pediatrics, 2020)
Abstract Attention is a major cognitive function that allows the individuals to focus selectively on a discrete stimulus while ignoring others. Visual information could be driven endogenously, when the goals or desires are voluntary, or exogenously, in response to salient visual events in the environment. Since subjects with attention deficit hyperactivity disorder (ADHD) show heightened distractibility during activities that require significant attentional engagement, we hypothesized that they may be more severely impaired in their ability to perform endogenous task than controls. To elicit endogenous and exogenous shifts of attention, we thus used a modified version of Posner’s cueing task. We compared oculomotor performance measured by an eye tracker in a group of 31 children with ADHD (mean age=9.1±1.3 years) and age- sex- and IQ- matched typically developing children. Endogenous and exogenous conditions were explored in three distinct visual sub-conditions (valid, invalid and neutral). We found that children with ADHD showed longer latency during endogenous conditions compared to TD children in invalid sub-condition. They also performed more errors than controls, during endogenous task in neutral sub-condition and during exogenous task in neutral and invalid sub-conditions. Our study suggests that children with ADHD may allocate their attention resource toward the detection of exogenous targets with a deficit in their ability to perform endogenous task. We suggest also that they have a difficulty in the engagement of inhibitory control system particularly during voluntary saccade performance. This could result from impaired interactions between the ventral and dorsal attention networks as well as in the frontal eye field, although neuroimaging studies are necessary to validate this hypothesis in ADHD population.